The Implementation of Teaching English Based on 2013 Curriculum at The Second Grade Students - Saputra Salman, Rendi; Prima Dewi, Merry (Journal of Educational Management and Strategy, 2023)
This research was based on the problems that was found about teaching English. The researcher found that the teacher seems to focus on the speaking ability of the students which make them hard to complete the task that is related to reading or other skills. The teacher admitted, to be able to speak properly was the main goal of the teacher for her student, and the teacher said if the students had a good ability to speak it would be a great chance for them to join many competitions such as speech and debate competition. The purpose of this research was to find out how teaching English based on curriculum 2013 at MAN 1 Bukittinggi is. The researcher used descriptive qualitative research design. The informant of the research was eleventh grade English teacher of MAN 1 Bukittinggi and the eleventh grade students of MAN 1 Bukittinggi. The key informant of this research was the English teacher of eleventh grade and the supporting informant was the eleventh grade students. The researcher took 30% of the eleventh grade as the sample which was 48 students. The sample was taken randomly. The instruments that were used in this research were, interview and questionnaire. The researcher found that the teacher teaches English based on curriculum, since the 2013 curriculum using the scientific approach and the teacher does the scientific approach too in the classroom. The problems that was encountered is the students do not search or learn the material before hand even though the teacher asked them to. They only gather information only from textbook. Furthermore the students motivation to ask question in the classroom is still low. Abstrak Penelitian ini didasarkan pada masalah yang ditemukan tentang pengajaran bahasa Inggris. Peneliti menemukan bahwa guru tampaknya fokus pada kemampuan berbicara siswa yang membuat mereka sulit menyelesaikan tugas yang berhubungan dengan membaca atau keterampilan lainnya. Guru mengakui, untuk dapat berbicara dengan baik adalah tujuan utama guru bagi siswanya, dan guru tersebut mengatakan jika siswa memiliki kemampuan berbicara yang baik maka akan menjadi kesempatan besar bagi mereka untuk mengikuti berbagai perlombaan seperti pidato dan kompetisi debat. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana pembelajaran bahasa Inggris berdasarkan kurikulum 2013 di MAN 1 Bukittinggi. Peneliti menggunakan desain penelitian kualitatif deskriptif. Informan penelitian ini adalah guru bahasa Inggris kelas XI MAN 1 Bukittinggi dan siswa kelas XI MAN 1 Bukittinggi. Informan kunci penelitian ini adalah guru bahasa Inggris kelas sebelas dan informan pendukung adalah siswa kelas sebelas. Peneliti mengambil 30% dari kelas sebelas sebagai sampel yaitu 48 siswa. Sampel diambil secara acak. Instrumen yang digunakan dalam penelitian ini adalah wawancara dan angket. Peneliti menemukan bahwa guru mengajar bahasa Inggris berdasarkan kurikulum, karena kurikulum 2013 menggunakan pendekatan saintifik dan guru juga melakukan pendekatan saintifik di dalam kelas. Permasalahan yang dihadapi adalah siswa tidak mencari atau mempelajari materi terlebih dahulu padahal diminta oleh guru. Mereka hanya mengumpulkan informasi dari buku teks. Selain itu motivasi siswa untuk bertanya di kelas masih rendah.